STUDENTS’ CRITICAL THINKING IN LEARNING AGREEMENT AND DISAGREEMENT USING DEBATE - Dewi, Fitriana; Setyaji, Arso; Ambarini, Ririn (Universitas 17 Agustus 1945 Semarang, 2024)
Critical thinking is important in learning English to understand and comprehend information. This study aims, first, to describe students’ critical thinking in learning agreement and disagreement using debate. Second, to describe the most component of critical thinking used by students in learning agreement and disagreement using debate. Last, to describe students’ perceptions of their critical thinking in learning agreement and disagreement using debate. The subject of this study is X PPLG 1 of SMK N 7 Semarang. This study uses a case study descriptive qualitative research method. The Researchers do observation, use video recording, and students’ work in collecting data. Also, we include students-interview to give validation in this study. In analyzing the data, we use five indicators of critical thinking, a theory from Ennis which are: Giving a simple explanation, Building fundamental skills, Concluding, Providing further explanation, set strategy, and technique. The findings of this study indicates that students can think critically and use five indicators of critical thinking in learning agreement and disagreement using debate. With mostly use of indicators; give a simple explanation and set strategies and techniques. The students combine small discussions and use translation apps in debate as critical thinking indicators of strategies and techniques. It is hoped that this research is useful in terms of implementing critical thinking in students. Critical thinking helps students learn deeper about information, especially English.